THE DETERMINANTS ON COST OF DEBT IN THE MANUFACTURING INDUSTRY - Wira Wijaya Gea; Suwinto Johan (Universitas Trisakti, 2021)
The manufacturing industry is the biggest contributor to the gross domestic product of Indonesia. The cost of debt is one of the factors for manufacturing companies in carrying out their operations. Lowering the cost of debt could attract manufacturing companies to raise funds through debt that will help the companies generate profit. This research figures out the impact of factors that may affect the cost of debt. This study is quantitative research that uses multiple regression as statistical analysis to test the hypotheses by using E-views 10 as a tool. The data population is manufacturing firms in Indonesia and samples are manufacturing firms listed on Indonesia Stock Exchange for 2015-2019. The results show that institutional ownership, debt to equity ratio, and interest coverage ratio impact the cost of debt. While managerial ownership, firm size, and return on assets do not impact the cost of debt.